The Enlightenment and religion : the myths of modernity - Barnett, S. J., 1960- (Manchester University Press ; Distributed exclusively in the USA by Palgrave, 2003)
The Enlightenment and religion: The myths of modernity offers a critical survey of religious change and its causes in eighteenth-century Europe, and constitutes a radical challenge to the accepted views in traditional Enlightenment studies. Focusing on E.